Learning to Attend Selectively: The Dual Role of Intersensory Redundancy. (December 2014) - Bahrick, Lorraine E.; Lickliter, Robert
Selective attention is the gateway to perceptual processing, learning, and memory and is a skill honed through extensive experience. However, little research has focused on how selective attention develops. Here, we synthesize established and new findings from studies assessing the central role of redundancy across the senses in guiding and constraining this process in infancy and early childhood. We highlight research demonstrating the dual role of intersensory redundancy—its facilitating and interfering effects—in the detection and perceptual processing of various properties of objects and events.